(untitled) (Journal of Chemical Engineering, 2013)
For reducing the post-harvest loss and extension of shelf-life of banana, it is treated with fungicide or combination of fungicide and hot-water treatment. A study was conducted for developing a method to control post-harvest diseases and extension of shelf-life of banana through non-chemical method of hot water treatment. The best treatment combination was found at 53 °C for 9 minutes. Shelf-lives of BARI Kola 1 and Sabri Kola treated with hot water increased by 26 and 27.5%, respectively against untreated fruits. Post-harvest loss (decay and crown rot) of these varieties was reduced, respectively by 95% and 70% against untreated fruits. Firmness of treated fruits for both varieties was found higher than that of untreated fruits during ripening. Total soluble solid, total sugar, acidity and ?-carotene of treated fruits of these varieties increased over untreated fruits. The pH and vitamin C of treated bananas decreased over untreated fruits during ripening. DOI: http://dx.doi.org/10.3329/jce.v27i1.15857 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 42-47